Health-related quality of life of salvage prostate reirradiation using stereotactic ablative radiotherapy with urethral-sparing - Greco, Carlo; Pares, Oriol; Pimentel, Nuno; Louro, Vasco; Nunes, Beatriz; Kociolek, Justyna; Marques, Joao; Fuks, Zvi (Frontiers in Oncology, 2022)
Purpose: to explore whether prostate motion mitigation using the rectal distension-mediated technique is safe and effective in stereotactic ablative radiation therapy (SABR) salvage treatment of intraprostatic cancer recurrences following initial radiotherapy for primary prostate cancer. Materials and Methods: Between July 2013 and December 2020, 30 patients received salvage SABR for 68Ga- PSMA-11 PET/CT-detected intra-prostatic relapses. Median time from primary RT to salvage reirradiation was 70.2 (IQR, 51.3-116.0) months. Median PSA at retreatment was 3.6 ng/mL (IQR, 1.9-6.2). Rectal distension-mediated SABR was achieved with a 150-cm3 air-inflated endorectal balloon and a Foley catheter loaded with 3 beacon transponders was used for urethra visualization and on-line tracking. MRI-based planning employed a 2-mm expansion around the planned target volume (PTV), reduced to 0-mm at the interface with critical organs at risk (OARs). Volumetric Modulated Arc Therapy (VMAT) permitted a 20% dose reduction of the urethra. VMAT simultaneous integrated boost (SIB) of the dominant intraprostatic lesion was deployed when indicated. Median SABR dose was 35 Gy (7 Gy per fraction over 5 consecutive days; range 35-40 Gy). Toxicity assessment used CTCAE v.4 criteria. Results: Median follow-up was 44 months (IQR, 18-60). The actuarial 3- and 4-year biochemical relapse free survival was 53.4% and 47.5%, respectively. Intraprostatic post-salvage relapse by PSMA PET/CT was 53.3%. Acute grade 2 and 3 genitourinary (GU) toxicities were 20% and 0%, respectively. There were no instances of acute grade ≥2 rectal (GI) toxicity. Late grade 2 and 3 GU toxicities occurred in 13.3% and 0% of patients, respectively. There were no instances of grade ≥2 late rectal toxicity. Patient-reported QOL measures showed an acute transient deterioration in the urinary domain 1 month after treatment but returned to baseline values at 3 months. The median IPSS scores rose over baseline (≥5 points in 53% of patients) between month 6 and 12 post-treatment as a result of urinary symptoms flare, eventually receding at 18 months. The bowel domain metrics had no appreciable changes over time. Conclusion: Pursuit of local control in intraprostatic failures is feasible and can be achieved with an acceptably low toxicity profile associated with effective OAR sparing.